Cancer-associated fibroblasts in carcinogenesis - Shufen Zhou; Zekun Zhao; Zhaojun Wang; Hanzheng Xu; Yijie Li; Ke Xu; Wei Li; Jiahua Yang (Journal of Translational Medicine)
Abstract In contemporary times, cancer poses the most significant threat to human life and safety. Scientists have relentlessly pursued the intricacies of carcinogenesis and explored ways to prevent and treat cancer. Carcinogenesis is a complex, multi-faceted, and multi-stage process, with numerous underlying causes, including inflammation and fibrosis. Cancer-associated fibroblasts (CAFs), however, occupy a pivotal and substantial role within the tumor microenvironment, facilitating carcinogenesis through diverse mechanisms such as creating inflammation, fostering a fibrotic tumor microenvironment, and immunosuppression. In this paper, we introduce the concept of carcinogenesis, explain its causes, describe the characteristics of CAFs and their sources, and highlight the roles and mechanisms of CAFs in promoting carcinogenesis. Ultimately, our aim is to contribute to the development of novel therapeutic strategies for cancer treatment.